Pertinent laws on hospitality management : tourism laws - Maranan, Mario H.; Maranan, Jovid Maricar David-;Rodriguez, Violeta V. (Intramuros, Manila, Philippines : Mindshapers Co. Inc., 2007)
Any organization would not stay long if it observes no rule, no standard, no system and no law.
Chapter 1. Constitutional provisions in the Hospitality world -- Chapter 2. Types of Business organization -- Chapter 3. Obligations and contracts -- Chapter 4. Hospitality at work -- Chapter 5. Laws and Travel -- Chapter 6. Tourism torts and damages -- Chapter 7. Accreditation of hospitality business.
Includes bibliographical references.
Keywords: HOSPITALITY INDUSTRY -- LAW AND LEGISLATION -- PHILIPPINES